Return to Play Rates of Young Athletes After Patellofemoral Instability Treatment. Issue 5 (31st May 2022) - Brenner, Madison; Cooper, Savannah; Johnson, Benjamin L.; Wyatt, Charles W.; Wilson, Philip L.; Ellis, Henry B.
Background: Following non-operative or operative treatment, many young patients with patellofemoral instability (PFI) desire to return to sport. The rate of return to play in young athletes following PFI treatment is not well known. Hypothesis/Purpose: To examine the return to play rates of skeletally immature and mature patients after either non-operative or operative treatment for PFI. Methods: Patients from a pediatric sports medicine clinic diagnosed with PFI prospectively followed over a 4+ year time frame were evaluated. Patients who had documented physical exam follow-up with a recorded date of return to play (RTP) were included in the study. Demographics, skeletal maturity, type of treatment, and physical exam details were included in the analysis. Results: Within this cohort of 62 knees, 35 of the 54 knees that played a primary sport (63.4%; mean age=14.87±2.02) ultimately returned to activity. 28 were skeletally immature (45.2%) and 34 were mature (54.8%). 5 knees received non-operative treatment (8.06%), and 57 received operative treatment (91.94%), including medial patellofemoral reconstruction, tibial tubercle osteotomy, and lateral release, among other procedures. 75.81% of patients were female, and 24.19% were male. The average time from PFI treatment to return to play was 236.48 days (±108.95). This time did not significantly differ between males and females, nor skeletally immature or mature knees (p=0.485; p=0.629). No physical exam points, such range of motion, J-sign, or patellar apprehension, were significant. Residual signs and symptoms were infrequent, but not absent at RTP: 11.1% positive apprehension, 8.5% mild J-sign, and 5.2% continued pain or instability in one or more locations on their knee at RTP. Significantly fewer skeletally mature patients returned to their primary sport after treatment (95.5% immature vs 40% mature, p<0.0001) not necessarily related to their knee or treatment. 32.76% of knees included had bilateral instability, which could increase average RTP if these athletes were not receiving simultaneous treatment. Conclusion: Over half of young athletes treated at a sports medicine clinic returned to play following PFI treatment.